1993
DOI: 10.1213/00000539-199310000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inotropic Effects of Amrinone and Epinephrine After Cardiopulmonary Bypass in Humans

Abstract: Amrinone, a phosphodiesterase inhibitor, and epinephrine, an alpha- and beta-adrenergic receptor agonist, are inotropic drugs used during cardiac surgery to reverse myocardial depression after cardiopulmonary bypass. However, these drugs have not been compared separately, or in combination, in this patient population. We hypothesized that the combination might have complementary actions in improving myocardial function. We, therefore, compared amrinone, epinephrine, and the combination of amrinone and epinephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…14,42,43 Combining milrinone with a direct B1R agonist may additively increase CO in patients with profoundly impaired cardiac function, with an added risk of adverse events. 24,47,48 Dobutamine Versus Milrinone Dobutamine and milrinone produce similar improvements in CO when titrated to full effect in patients with HF, although each individual patient may respond better to one drug or the other. 41,[49][50][51] Dobutamine produces greater stimulation of myocardial contractility, while milrinone produces greater vasodilation and reduction in cardiac filling pressures (Table 2).…”
Section: Goals Of Resuscitationmentioning
confidence: 99%
“…14,42,43 Combining milrinone with a direct B1R agonist may additively increase CO in patients with profoundly impaired cardiac function, with an added risk of adverse events. 24,47,48 Dobutamine Versus Milrinone Dobutamine and milrinone produce similar improvements in CO when titrated to full effect in patients with HF, although each individual patient may respond better to one drug or the other. 41,[49][50][51] Dobutamine produces greater stimulation of myocardial contractility, while milrinone produces greater vasodilation and reduction in cardiac filling pressures (Table 2).…”
Section: Goals Of Resuscitationmentioning
confidence: 99%
“…Two small, randomized controlled trials [5,8] compared epinephrine with the PDI amrinone. In both studies, both drugs significantly increased CI from baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Usually amrinone causes a positive inotropic effect when it is administered to maintain a therapeutic plasma concentration of 1.5-2.0[~g-m1-1 [1][2][3][4]. In ischemia-damaged hearts, 1009g.ml 1 amrinone had an apparent inotropic action, provoking significant increases in cardiac output (11%) and aortic flow (10%) in the isolated working rat heart [20].…”
Section: Discussionmentioning
confidence: 99%
“…Amrinone may be useful to treat the clinical patients with poor left heart function after cardiopulmonary bypass and patients with heart failure associated with acute myocardial infarction. In previous studies, amrinone was reported to improve cardiac performance in patients undergoing cardiac surgery [1][2][3][4]. In those studies, the effects of amrinone were modified by autonomic sympathetic and parasympathetic reflexes.…”
mentioning
confidence: 96%